Community‐delivered infant–parent psychotherapy improves maternal sensitive caregiving: Evaluation of the Michigan model of infant mental health home visiting. Issue 2 (3rd April 2020) - Rosenblum, Katherine L.; Muzik, Maria; Jester, Jennifer M.; Huth‐Bocks, Alissa; Erickson, Nora; Ludtke, Mary; Weatherston, Debbie; Brophy‐Herb, Holly; Tableman, Betty; Alfafara, Emily; Waddell, Rachel; ,
ABSTRACT: The current study evaluated the effectiveness of a home‐based psychotherapeutic Infant Mental Health Home Visiting (IMH‐HV) intervention for enhancing parenting sensitivity; a secondary aim was to evaluate whether the use of video feedback was associated with greater treatment response. Participants were N  = 78 mothers and their children (age at entry ranged from prebirth to 24‐month old ( M  = 9.8, SD  = 8.4), who were initiating IMH‐HV services with community mental health‐based therapists ( N  = 51). Dyads were assessed during extended home visits via standardized interviews and observational and questionnaire methods within the first month of treatment (baseline), and again 6 and 12 months thereafter. Following each of these extended home visits, study evaluators completed a standard Q‐sort to capture observations of maternal sensitivity during the visit. Therapists completed fidelity checklists used to derive the total number of IMH‐HV sessions received (i.e., dosage) and frequency with which therapists provided video feedback. Results indicated a dose–response relationship between number of sessions and maternal sensitivity, and that video review with parents independently contributed to improved maternal sensitivity. Discussion focuses on the effectiveness of this community‐based psychotherapeutic home visiting model for enhancing parenting, as well as the value of video feedback as a specific therapeutic strategy.